THE EFFECT OF SERVICE AND PRODUCT QUALITY ON CUSTOMER SATISFACTION AT PD JAYA SENTOSA ABADI - Aurelia Putri Indrawan; Muhammad Bintang Marthajaya; Prihartono Prihartono (Media Bina Ilmiah, 2022)
The increasingly fierce business competition in the clothing sector forces business actors to maximize and utilize operational efficiency through service and product quality as best they can in order to survive in business competition and be able to create customer satisfaction. This study aims to determine the effect of service and product quality on customer satisfaction at PD Jaya Sentosa Abadi. The research method used is quantitative research and analysis technique using multiple linear regression. Explains that the effort in service (x1) and product quality (x2) which has a value of 0.127 and 0.186 can increase customer or consumer satisfaction by 0.669. Using the SPSS calculation shows a value of 0.00 <0.05, which means that service and product quality affect customer satisfaction. The results showed that service quality and product quality had a positive and significant effect on customer satisfaction at PD Jaya Sentosa Abadi.